Mesoporous multi-valence manganese oxides composite nanotubes boosting long-life lithium-ion batteries. Issue 48 (30th November 2022) - Zhou, Junxiang; Feng, Bo; Kong, Xiangze; Li, Lei; Li, Zhiqiang; Tian, Xiaoxia; Feng, Mingde; Qu, Shaobo; Wang, Jiafu
Abstract : Multi-component nano-oxide composite materials may present special synergistic effects as anode materials for lithium-ion batteries. Abstract : Multi-component nano-oxide composite materials may present special synergistic effects as anode materials for lithium-ion batteries. Mesoporous β-MnO2 /Mn3 O4 composite nanotubes are built here via controlling the deoxidation process of carbon-coating to induce a partial phase transition of high valence manganese dioxides. Compared to single β-MnO2 nanotubes or Mn3 O4 @C nanotubes, the mesoporous β-MnO2 /Mn3 O4 @C composite nanotubes exhibit superior electrochemical properties. 679 mA h g −1 of reversible specific capacity and 86% of capacity retention after 1000 cycles at 1 A g −1 current density are obtained. The excellent performance is attributed to the unique multiple phase transitions regulation phenomena of manganese oxide occurring in the β-MnO2 /Mn3 O4 composite material during the electrochemical processes, which significantly extends the cycle life of the β-MnO2 /Mn3 O4 composite material.